Effect of Kappaphycus Alvarezii in Development of Functional Based Reformulated Chicken Sausages Utilizing Spent Hen Meat: 10.5958/2581-6616.2020.00016.X - Biswas, P.; Biswas, A.K.; Mandal, A.B. (Journal of Meat Science, 2020)
Development of functional based reformulated chicken sausage is a newer challenge since this type of product not only contributes functional health attributes but also improves or at least retains product’s quality. So, a research study was undertaken to develop a functional chicken sausage with incorporation of Kappaphycus alvarezii (KP-A) powder. KP-A was added in the formulation at 0 (Control), 0.5 (T1), 0.75 (T2) and 1.0 (T3) % levels, mixed separately, encased in casings and finally, water cooked. The products were evaluated for different physicochemical quality, antioxidant activity, instrumental color and sensory quality parameters. Result showed that cooking yield was significantly (P0.05) differences in redness (a-value), yellowness (b-value) Hue and Chroma values amongst the treated samples and control. However, incorporation of KP-A in the product formulations showed only numerical increase in ABTS+ and DPPH activity. Sensory evaluation parameters revealed that T1 and T3 samples scored nearly similar but the scores for T2 sample were higher for all attributes than control, T1 and T3. Thus, it was concluded that addition of KP A has greater role in improving functional health attributes of chicken sausage besides its contribution in improving product quality.
Keywords: Kappaphycus alvarezii; Functional chicken sausage; Reformulated meat product; Antioxidant activity; Meat color